2010
DOI: 10.1093/bja/aeq096
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia with parecoxib, acetaminophen, and the combination of both: a randomized, double-blind, placebo-controlled trial in patients undergoing thyroid surgery

Abstract: Parecoxib and acetaminophen effectively reduce postoperative opioid requirements after thyroid or parathyroid surgery. The combination of these drugs is not associated with a further reduction in opioid consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
4
18
0
2
Order By: Relevance
“…In our present study, parecoxib analgesia resulted in an average reduction of cumulative morphine requirements by 24% compared to placebo in patients undergoing open prostatectomy. This finding is in accordance with previous studies describing an opioid sparing effect of COX-2 inhibitors in the postoperative period [8-13]. However, opioid sparing is not by itself considered a clinically meaningful endpoint [7,28].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our present study, parecoxib analgesia resulted in an average reduction of cumulative morphine requirements by 24% compared to placebo in patients undergoing open prostatectomy. This finding is in accordance with previous studies describing an opioid sparing effect of COX-2 inhibitors in the postoperative period [8-13]. However, opioid sparing is not by itself considered a clinically meaningful endpoint [7,28].…”
Section: Discussionsupporting
confidence: 92%
“…Selective cyclooxygenase-2 (COX-2) inhibitors have been proposed to be a safe alternative for several years. Parecoxib (a prodrug of valdecoxib) is a parenterally selective cyclooxygenase-2 (COX-2) inhibitor that reduces postoperative opioid consumption, following thyroid surgery [8], hernia repair [9], gynecological laparotomy [10], total hip [11] and knee arthroplasty [12], as well as spine surgery [13]. However, the use of parecoxib in cardiac surgery has been associated with an increased incidence of cardiovascular events in at-risk patients [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Our study is comparable with the study conducted by M. Gehling et al (2010), 28 who in their study concluded that parecoxib, acetaminophen and their combination reduced postoperative opioid requirement significantly by 50% (p<0.05). However, the combination of parecoxib and acetaminophen is not associated with a further reduction in opioid consumption.…”
Section: Graph 3: Showing Episodes Of Nausea and Vomiting In Studied supporting
confidence: 92%
“…concluded that single parenteral injection of parecoxib 40 mg compares favorably with two infusions of propacetamol 2 g within the first 12 in adult patients. [1718] The COX-2 selective NSAIDs rofecoxib or celecoxib usually demonstrated analgesic efficacy superior to paracetamol when given orally. [1920]…”
Section: Discussionmentioning
confidence: 99%